Development of the Pancasila Student Profile Strengthening Project Module Based on Regional Potential on Sustainable Lifestyle at SMA N 3 Rupat - Siti Nur Syafiqa; Elvy Rahmi Mawarnis; Dwivelia Aftika Sari; Mohd. Yusri Abd. Rahman (International Journal of Contextual Science Education, 2025)
Education in the era of the independent curriculum emphasizes the importance of forming student character through strengthening the profile of Pancasila students. The implementation of the Pancasila Student Profile Strengthening Project allows students to learn from real problems in their environment. Sustainable lifestyle is one of the important themes in the Pancasila student profile strengthening project which aims to instill awareness and concern for the preservation of the surrounding environment. However, in practice, there are still many schools that face obstacles in implementing this theme in a relevant and meaningful way, especially due to the lack of learning guidelines that are in accordance with the potential of the region. The development of a project module to strengthen the profile of Pancasila students based on regional potential is the right solution to answer these challenges. This research uses research and development  methods with a 4-D development model (define, design, develop and disseminate). Data collection was carried out through interview methods and questionnaire distribution. The data analysis technique used is validity and practicality analysis. The results of the study showed that the validity test of the Pancasila student profile strengthening project module based on regional potential on the theme of sustainable lifestyle at SMA N 3 Rupat met the very valid criteria with a score percentage of 88% and very practical with a score percentage of 86%. Based on these results, it can be seen that the learning process becomes more meaningful because students not only learn concepts, but also apply them in the real form of rubber tree seed waste processing. The implementation of the module shows an increase in mutual cooperation, independence, and concern for the environment in students. Based on the results of the research, it can be concluded that the project module for strengthening the Pancasila student profile based on regional potential on the theme of sustainable lifestyle is very valid and practical and can be used as a guide in carrying out project activities to strengthen the profile of Pancasila students in schools so that it can foster environmental awareness and social responsibility of students. Further research can be directed towards the development of cross-thematic modules, for example combining the theme of sustainable lifestyle with entrepreneurship to foster an innovative spirit and creative economy in students.